SISTEM APLIKASI PELAPORAN KEGIATAN UKM MUSIK DI UNIVERSITAS LIA DENGAN METODE WATERFALL - Intan Murniasih; Ariya Pannadhitthana Candra; Ade Davy Wiranata (ISTEK WIDURI, 2025)
The Music Student Activity Unit (UKM) is one of the UKM that accommodates student organizations in universities to hone the skills of members and administrators in channeling the talents and interests of students in the field of music arts, ranging from traditional music to modern music to be staged in order to preserve culture through certain events both held at LIA University and off-campus events. This study discusses the application used for reporting music UKM activities at LIA University using the Waterfall model. The purpose of creating this application is to make it easier to report on music UKM activities, especially at LIA University. In addition, this application can also accelerate decision-making in the organization of the music UKM. The waterfall model in this study was chosen because it can adapt to the changing needs of music UKM users. The process of creating this application is made through several stages, namely: system needs analysis, design, implementation/coding, testing, evaluation. The results of this study are in the form of an application with features for reporting activities, as well as a dashboard of music UKM activity reports. Application trials show that users find it easier to report and access information on activities carried out by music UKM administrators. Users consisting of administrators and members of music UKM. This trial aims to get feedback on the functionality and interface of the app. The test results show that: 95% of users feel that the app is easy to use and the interface is intuitive. 90% of users stated that the activity reporting feature is very helpful in documenting music UKM activity reports, especially at LIA University. 85% of users appreciate the notification feature that helps them remember reporting deadlines. However, some users also provided feedback for improvements, including: Added a feature to upload photos of activities. Increased app access speed during peak hours. This research is expected to make a positive contribution to the development of applications within LIA University, especially music UKM.